Protective Roles of Monsonia angustifolia and Its Active Compounds in Experimental Models of Alzheimer's Disease - Chun, Yoon Sun; Kim, Joonki; Chung, Sungkwon; Khorombi, Eric; Naidoo, Dashnie; Nthambeleni, Rudzani; Harding, Nial; Maharaj, Vinesh; Fouche, Gerda; Yang, Hyun Ok (American Chemical Society, 2017)
Alzheimer's disease (AD), a progressive neurodegenerative disorder,, is characterized by the accumulation of neurotoxic beta-amyloid (A beta) peptides, which consequently affects cognitive decline and memory impairment. Current research on AD treatment is actively focusing on the prevention of neurotoxic A beta peptide accumulation. Monsonia angustifolia is reported to be consumed as an indigenous vegetable in Tanzania. In this study, we investigated the effect of the ethanol (EtOH) extract of M. angustifolia dried ground material on A beta production and spatial learning ability as protection against AD. The formation of A beta peptides was significantly reduced in HeLa cells stably transfected with the Swedish mutant form of,beta-amyloid precursor protein (APPsw) after treatment with a 60% EtOH extract of M. angustifolia. We next examined the cognitive-improving effects of the EtOH extract in vivo. Tg2576 mice were treated with extract for 6 months and subjected to Morris water maze and novel object recognition tests. The results showed that the 60% EtOH extract of M. angustifolia significantly ameliorated behavioral deficits of the AD transgenic mice and reduced the level of insoluble A beta 42 in the cerebral cortex and hippocampus. We further found that the 60% EtOH extract was effective for memory function recovery after shorter treatment (4 months). In addition, we isolated and identified several single compounds, justicidin A, 5-methoxyjusticidin A, chinensinaphthol, retrochinensinaphthol methyl ether, and suchilactone, from M. angustifolia and tested these compounds. Among them, justicidin A potently decreased the formation of A beta in APPsw-transfected cells. These data suggest that the 60% EtOH extract of M. angustifolia has the potential to be developed as a treatment of AD. Furthermore, justicidin A may contribute, at least partially, to the A beta alteration observed with the extract treatment.